Mass spectrometry characterization of Commiphora leptophloeos leaf extract and preclinical evaluation of toxicity and anti-inflammatory potential effect - Dantas-Medeiros, Renato; Furtado, Allanny Alves; Zanatta, Ana C. [UNESP]; Torres-Rêgo, Manoela; Guimarães Lourenço, Estela Mariana; Ferreira Alves, Jovelina Samara; Galinari, Éder; Alexandre de Oliveira Rocha, Hugo; Bernardo Guerra, Gerlane Coelho; Vilegas, Wagner [UNESP]; Antônio de Sousa Araújo, Thiago; de Freitas Fernandes-Pedrosa, Matheus; et al. (Elsevier, 2021)
Ethnopharmacological relevance: Commiphora leptophloeos (Mart.) J.B. Gillett (Burseraceae) is a medicinal plant native from the brazilian northeast caatinga biome, known popularly as “imburana” or “imburana-de-cambão”. The leaves of C. leptophloeos are widely used in folk medicine in the treatment of various inflammatory disorders. However, there is no scientific evidence to justify their popular use. Aim of the study: This approach aimed to characterize the phytochemical profile of hydroethanolic leaf extract, as well as evaluate the anti-inflammatory and antioxidant potential activity and to investigate the acute toxicity with pre-clinical in vitro and in vivo methodologies. Materials and methods: The phytochemical profile was characterized by UPLC-MS and FIA-ESI-IT-MS/MS. The in vitro anti-inflammatory potential the hydroethanolic extract of C. leptophloeos (1, 10, 100 and 200 μg/mL) was investigated by lipopolysaccharide (LPS) induced nitric oxide assay, in order to analyze the potential decrease of nitric oxide (NO) production. For carrageenan-induced paw edema and zymosan-induced air pouch models, the extract (100, 200 and 400 mg/kg) was administrated by intragastric gavage (i.g.) route and used for evaluating the anti-inflammatory effect in vivo. Related to the first animal model, the antiedematogenic activity and myeloperoxidase (MPO) levels could be investigated. In addition, the zymosan-induced air pouch model allowed the analyses of leukocytes migration, total MPO, malondialdehyde (MDA) and cytokines (TNF-α and IL-10) levels. The toxicity in vitro of the extract (1, 10, 100 and 200 μg/mL) was evaluated using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and acute toxicity in vivo was tested using the extract at 2000 mg/kg by i. g. route. Results: The phytochemical analyses of C. leptophloeos leaf extract pointed the presence of six glycosylated flavonoids, identified as orientin, isoorientin, vitexin and isovitexin, quercetrin and isoquercitrin. A decrease of NO in vitro was noticed by the use of the extract in the LPS-induced nitric oxide assay and an expressive reduction of the paw-edema followed by a decrease of myeloperoxidase activity at doses of 200 and 400 mg/kg. The zymosan-induced air pouch model indicated that the extract, in all doses, significantly reduced the leukocytes migration, total protein concentration, MPO and MDA levels. The levels of cytokines were verified by the administration of extract in this model, revealing a lower of TNF-α level and an increase of the IL-10 production. In the toxicity study, the MTT assay evidenced no cytotoxicity of the tested concentrations and acute toxicity in vivo test did not result in any sign of toxicity and mortality or significant changes on the biochemical parameters. Conclusion: Based on these results, is possible suggest that the anti-inflammatory activity revealed in this approach can be related to the modulating the level of cytokine, decrease of TNF-α, increase of IL-10 in vivo and also the inhibition of the production of nitric oxide RAW 264.7 activated by LPS. These results demonstrate the potential anti-inflammatory effect C. leptophloeos leaf extrat in inflammatory in vivo models, supporting its use in folk medicine for treatment of inflammatory diseases. Finally, glycosylated flavonoids can be responsible, at least in part, for this effect.
Keywords: Antioxidant; Commiphora leptophloeos; Flavonoids; Imburana; Inflammation; Toxicity